The Roles Of Rapid Penang Towards Sustainability Public Transportation In Penang - Sharom, Noorashikin (2014)
It is important for public transportation provider to playa role in justifying the sustainability of public transportation in Penang. This is mainly because of the C02 emissions of vehicles that come from the congested traffics especially in Penang where it is now at the critical stage. Improved public transport infrastructure is one of the major goals for any congestion plan. This research is to investigate, explore and measure the roles of Rapid Penang towards making the sustainable transportation a success in the state. Poor management, especially when the cost is rising up, will lead to poor service, unsatisfied passengers, unsatisfied employees, lower pay, internal dissatisfaction, job delay, human error and wasted infrastructure. It is useful to know the main strengths and weaknesses of the public transportation provider which is useful to make the effort for sustainable transportation and solving the problems in Rapid Penang and indirectly also becoming the solution of the traffic congestion problem in Penang. Through the dimensions of important roles plays by Rapid Penang which is customer satisfaction, professionalism among their employees, efficient and good management, and sustainable public transportation can be improved.